Impact of chronic opioid use on acute health care utilization in children with IBD and arthritis: a retrospective cohort study - Atiye O. Bilgic Dagci; Shunzhou Jiang; Joyce C. Chang; Andrew B. Grossman; Rui Xiao; Pamela F. Weiss (BMC, 2024)
Abstract Background Opioid use is non-trivial in children with inflammatory bowel disease (IBD) and arthritis, and options are limited for pain management. We aimed to determine the impacts of chronic opioid use on acute care utilization in children with both IBD and arthritis in United States. Methods Participants less than 18 years of age with IBD and arthritis, with at least one year of continuous enrollment (no interruption of insurance for at least 1 year) and at least one pharmacy claim in the Truven Health MarketScan Claims and Encounter Database, were included in the study. The primary exposure was chronic opioid use. Chronic opioid users were matched to non-exposed controls. The primary outcome was acute healthcare utilization (total number of emergency department visits and hospitalizations within 12-24 months after the index date). The association between acute care utilization and chronic opioid use was assessed using a multivariable negative binomial regression model. Results 480 children with IBD and arthritis met inclusion criteria, out of which 59 (12.3%) met the criteria for chronic opioid exposure, and 46 of them had at least one year of follow-up. IRR (incidence rate ratio) of acute healthcare use for patients exposed to chronic opioid use was 1.7 higher than controls. Additionally, public insurance and having a chronic pain condition were independently and significantly associated with greater acute healthcare use. Conclusion Chronic opioid use was significantly associated with greater acute health care utilization in children with IBD and arthritis than matched unexposed controls. Future investigation is warranted to determine if preferential use of non-opioid therapy for pain control can reduce acute healthcare costs in this population.